Effect of iterative reconstruction and temporal averaging on contour sharpness in dynamic myocardial CT perfusion: Sub-analysis of the prospective 4D CT perfusion pilot study - Feger, Sarah (PLoS One, 2018)
PURPOSE: Myocardial computed tomography perfusion (CTP) allows the assessment of the functional relevance of coronary artery stenosis. This study investigates to what extent the contour sharpness of sequences acquired by dynamic myocardial CTP is influenced by the following noise reduction methods: temporal averaging and adaptive iterative dose reduction 3D (AIDR 3D). MATERIALS AND METHODS: Dynamic myocardial CT perfusion was conducted in 29 patients at a dose level of 9.5±2.0 mSv and was reconstructed with both filtered back projection (FBP) and strong levels of AIDR 3D. Temporal averaging to reduce noise was performed as a post-processing step by combining two, three, four, six and eight original consecutive 3D datasets. We evaluated the contour sharpness at four distinct edges of the left-ventricular myocardium based on two different approaches: the distance between 25% and 75% of the maximal grey value (d) and the slope in the contour (m). RESULTS: Iterative reconstruction reduced contour sharpness: both measures of contour sharpness performed better for FBP than for AIDR 3D (d = 1.7±0.4 mm versus 2.0±0.5 mm, p>0.059 at all edges; m = 255.9±123.9 HU/mm versus 160.6±123.5 HU/mm; p<0.023 for all edges). Increasing levels of temporal averaging degraded contour sharpness. When FBP reconstruction was applied, contour sharpness was best without temporal averaging (d = 1.7±0.4 mm, m = 255.9±123.9 HU/mm) and poorest for the strongest levels of temporal averaging (d = 2.1±0.3 mm, m = 142.2±104.9 HU/mm; comparison between lowest and highest temporal averaging level: for d p>0.052 at all edges and for m p<0.001 at all edges). CONCLUSION: The use of both temporal averaging and iterative reconstruction degrades objective contour sharpness parameters of dynamic myocardial CTP. Thus, further advances in image processing are needed to optimise contour sharpness of 4D myocardial CTP.